Die homiletiek van Karl Barth - Dreyer, T. F. J. (Hervormde teologiese studies, 1987)
Karl Barth's homiletical viewsKarl Barth is well-known for his theology and dogmatics. His struggle as a young preacher to proclaim the word of God, inspired his theological views, especially his homiletics. This paper is an attempt to pay tribute to his homiletical views. In order to do this research it is necessary to evaluate his works against the background of the theological trends of his time. The conclusions of this paper are formed by putting Barth's homiletical principles to the test, comparing them ith abstracts from his sermons.